أحكام التوائم الملتصقة في الشريعة الإسلامية - صلوبة, صفاء; بوقنة, مروة (University of Eloued-جامعة الوادي, 2016)
هذا البحث دراسة حول موضع التوأم المتلاصق والذي بعنواون "أحكام التوائم الملتصقة في الشريعة الإسلامية" حيث تطرقنا إلى مفهوم التوائم الملتصقة فبدأنا بذكر تعريف التوائم والإلتصاق ثم سرد نشأته ونبذة تاريخية عنه وأسباب ولادتها ثم ذكرنا أنواع التوائم، ثم تطرقنا إلى أحاكم مختلفة متعلقة بالتوائم الملتصقة حيث بدأنا بحكم إجهاضها وجراحة فصلها ثم إلى مسألة إستقبال القبلة ومن ثم مسألة عدهم في صلاة الجمعة ومسألة السجود بالأعضاء السبعة إلى أحكام نكاحها ومسائل في باب ميراث التوائم الملتصقة ثم إلى جناية التوائم. summary of the research. This research is a consideration about of conjoined twins with title of " conjoined twins and provisions of Islamic Sharia" whereas we have talked about the concept of conjoined twins.We began by mentioning the definition of twins and the adhesion , then we recited about its birth, History and the reasons encountered it , therefore the types of twins.Then we spoke about different judges that related to the conjoined twins where we started by the verdict of abortion surgery or its separation , going to the issue of the orientation into Al-Kiblah and enumeration in the Friday prayers and the issue of the seven necessary members of prostration, the verdicts of wedding ,the legacy and the crimes of conjoined twins
مذكرة ليسانس
Keywords: التوائم /الملتصقة/أحكام; Jumeaux siamois/provisions